2019
DOI: 10.1186/s40337-019-0249-z
|View full text |Cite|
|
Sign up to set email alerts
|

Dimensions within 24 weight history indices and their association with inpatient treatment outcome in adults with anorexia nervosa: analysis of routine data

Abstract: Objective Next to weight suppression (WS), there are a range of less often examined weight history indices, and improvements to the WS construct have been proposed. We aimed to examine redundancy and overlap between 24 weight history indices in order to identify suitable constructs for further investigation. Method Analysis of routine data of 770 female adult inpatients treated for AN. Twenty-four indices based on highest, lowest, and current weight, as well as developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…Together with a high prevalence of ON in anorexia nervosa [14], this finding cannot easily be reconciled with the proposition that restrictive eating in ON is not aimed at weight loss but at healthy eating [1]. However, there was no association between orthorexic tendencies and measures of past and present weight in our sample, unlike to what is known from eating disorders [28,29]. Also, the lack of an association between orthorexic tendencies and symptoms of anorexia nervosa in our sample does not concur with what is reported for clinical and non-clinical samples (see Table 1; [13,14]).…”
Section: Discussioncontrasting
confidence: 83%
“…Together with a high prevalence of ON in anorexia nervosa [14], this finding cannot easily be reconciled with the proposition that restrictive eating in ON is not aimed at weight loss but at healthy eating [1]. However, there was no association between orthorexic tendencies and measures of past and present weight in our sample, unlike to what is known from eating disorders [28,29]. Also, the lack of an association between orthorexic tendencies and symptoms of anorexia nervosa in our sample does not concur with what is reported for clinical and non-clinical samples (see Table 1; [13,14]).…”
Section: Discussioncontrasting
confidence: 83%
“…While not every study provided details on the gender of the patients, 97.55% of the population in 24 studies were female [ 31 , 33 50 , 52 56 ]. Employment status was reported in five studies [ 30 , 40 , 42 , 44 , 48 ], revealing that about 47.5% were students, 25.67% were employed, and 15.72% were unemployed. The average age of patients in the 26 studies that reported this information was 27.22 years [ 30 – 34 , 36 56 ] and the mean length of inpatient stay in 18 studies was 59.35 days [ 30 , 33 , 34 , 37 , 38 , 40 42 , 44 51 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Employment status was reported in five studies [ 30 , 40 , 42 , 44 , 48 ], revealing that about 47.5% were students, 25.67% were employed, and 15.72% were unemployed. The average age of patients in the 26 studies that reported this information was 27.22 years [ 30 – 34 , 36 56 ] and the mean length of inpatient stay in 18 studies was 59.35 days [ 30 , 33 , 34 , 37 , 38 , 40 42 , 44 51 , 54 , 55 ]. Diagnosis subtype was specified in only 20 of the referenced studies [ 30 , 33 , 37 50 , 52 55 ], with about 57.16% corresponding to the restrictive type of AN, and 40.73% to the binge-purging type.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations